General observations and summary comments on monitoring data : visit to McIntyre closure sites including tailings pond plus superficial inspection of ERG tailings site : Timmins August 18-19, 2003 -- meetings with Joint Venture and site visits. - Michael P. Sudbury Consulting Services; Boojum Research Limited; Joint Venture Group (Boojum Research Limited, 2003)
Report provides information about the ERG tailings areas and water quality in the Porcupine river.